Kesiapan Guru Bimbingan dan Konseling Menjalani Penilaian Kinerja Guru - Mirza Mirza; Prayitno Prayitno; Daharnis Daharnis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2013)
The aim of this research is to reveal the readiness of guidance and counseling teachers toward Teacher’s Performance Assesment (TPA) at the quality of their understanding and attitude by using quantitative-descriptive method.The subject of this research is all guidance and counseling teachers at State Senior High Schools and State Vocational High School in Batu Bara District, North Sumatera Province. The number of the research subjects is 33 persons. Semantic differential model scale is the instrument being used in this research to measure the understanding and attitude of research subjects toward TPA.Statistic technique of Mann Whitney U is used to compare the data of two independent samples, and of Kruskal Wallis One Way Anova is used to compare the data of more than two independent samples, and Correlation Product Moment to see the correlation of the data.Based on the results of data analysis, it can be concluded that the readiness scores of research subjects toward TPA are not in good category